Value‐Added Recycling of Inexpensive Carbon Sources to Graphene and Carbon Nanotubes. (14th June 2018) - Kwon, Sung‐Joo; Seo, Hong‐Kyu; Ahn, Soyeong; Lee, Tae‐Woo
Abstract: Various methods are described here to synthesize functional carbonaceous materials (e.g., graphene and carbon nanotubes) from carbon waste for use in future optoelectronics. An ability to fabricate these materials from such inexpensive precursors would be economically beneficial. It also reviews attempts to improve the electrical properties of these materials, then discusses their practical electronic applications. Finally, future prospects for these processes are presented. Abstract : Recycling carbon waste into value‐added carbonaceous functional materials (graphene and carbon nanotubes) is of prime importance. The methods to synthesize functional carbonaceous materials from waste are reviewed, and then future perspectives to improve the productivity and quality of the carbonaceous functional materials for electronic application are discussed.